Seminar and Beauty Class: “Care about Beauty, Care about Health” Health and Beauty Education for Muslim Women - Fitri Anisa Kusumastuti; Muh. Khaedir Lutfi; Nadya Amalia Juana; Fitri Rizkiyah; Sonya Trikandi; Rizqi Nur Rachmawati; Mona Anju Sansena; Dwi Nova Holisiah (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2025)
Health and beauty are essential aspects of a Muslimah’s life, which Islamic values should maintain as a form of gratitude and responsibility for the body entrusted by Allah. However, a lack of education regarding proper, healthy, and halal self-care practices remains an issue. This community service program aims to enhance Muslim women's understanding of healthy and Islamic-compliant skincare through a seminar and beauty class themed